PENGEMBANGAN LEMBAR KERJA SISWA (LKS) DISERTAI GAMBAR PADA MATERI SISTEM REPRODUKSI MANUSIA UNTUK SMP - Gusrani, Gusrani; Risdawati, Renny; Susanti, Diana (Pendidikan Biologi, 2014)
ABSTRACTÂ In teaching and learning process requires a media that is able to achieve the learning objective. Worksheet used in the school is design by MGMP biology teacher Padang. Worksheet havenât attractive display. One of material biology in class IX4 junior high school is system reproduction. The display picture in worksheet havenât colour and clear. Based on explanation before the am of the study is to produce a worksheet with picture at system reproduction valid and practical. This research to do in SMPN 31 Padang grade IX4 on januari 23, 2014. This is research is the development of a 4-D models, consist of define, design, develop and disseminate. The data of this study in primary data. The validity of test data and test result practicalities. Validity data and practcalities is in the form percentage is descriptive. The result of classified worksheet valid by validators 84,00 %, and practical categorized by teachers 84,65%, and by students categorized as very practical 86,35%. From this study produced worksheet with picture comes on the material system reproduction valid and practical.Â